Implementation of General Principles of Good Government in Decision Number 8/G/2013/PTUN-KPG - Rasji, Rasji; Tanujaya, Calista Putri; Rigel, Rigel (CV. Rayyan Dwi Bharata, 2024)
Law Number 5 of 1986 concerning State Administrative Courts was established to be a guide for everyone in carrying out justice involving State Administrative Disputes. The juridical control that the PTUN has over State Administrative Decisions can reflect the implementation of government affairs by statutory regulations. The State Administrative Court which acts as an institution of judicial power which is directly under the Supreme Court (MA) must of course provide justice in the community as a public servant so that a balance is maintained between a person and other public interests and upholds the rights of the community to provide certainty. law. PTUN is also obliged to uphold the implementation of good governance. The General Principles of Good Government are one of the foundations for creating justice in resolving State Administrative Disputes and as a guideline in issuing various decisions that will be issued by government officials. The application of the principle of legal certainty in deciding a case is one of the important requirements that must be implemented by the Panel of Judges. Law Number 30 of 2014 concerning Government Administration provides an expansion of the PTUN's authority to examine and decide regarding deviations in the implementation of the AUPB. This writing aims to see whether the AUPB has been implemented properly in the issuance of State Administrative Decrees. The data we will examine in this writing is the Kupang State Administrative Court Decision Number 8/G/2013/PTUN-KPG.